Non-sterile examination gloves and sterile surgical gloves: which are more sustainable?. (December 2021) - Jamal, H.; Lyne, A.; Ashley, P.; Duane, B.
Summary: Background: Healthcare professionals should consider environmental sustainability when using personal protective equipment (PPE). One of the most frequently used items of PPE in medical settings are gloves. Aim: This study aims to quantify the environmental impact of sterile versus non-sterile gloves using the life cycle assessment (LCA) methodology. Methods: This study used three glove types: non-sterile gloves and sterile gloves (latex and latex-free). Sixteen different environmental impact categories were used to demonstrate the impact of each glove type. Findings: Non-sterile gloves had the least environmental impact in all categories. The two types of sterile gloves, non-latex (synthetic rubber) and latex (natural rubber), performed similarly, although the non-latex gloves had a greater impact on ozone depletion, mineral use and ionizing radiation. For climate change impact, sterile latex gloves were 11.6 times higher than non-sterile gloves. This study found that for both sterile type gloves (latex and non-latex), the manufacture of the gloves contributes to the most considerable environmental impact, with an average of 64.37% for sterile latex gloves and 60.48% for non-latex sterile gloves. Conclusion: Using the LCA methodology, this study quantitatively demonstrated the environmental impact of sterile versus non-sterile gloves.